Implementasi Digitalisasi Laporan Produksi Harian di Industri Manufaktur Untuk Meningkatkan Efisiensi dan Akurasi Data - Wely Teguh Setyawan; Hendi Herlambang; Tri Ngudi Wiyanto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The development of science and technology is increasingly rapid, including in the industrial world in the production and manufacturing sectors, technology is increasingly used in improving company performance. In the Manufacturing Industry, including the Fast-Moving Consumer Goods (FMCG) sector, it continues to strive to improve operational efficiency and productivity. This digitalization has been key in this effort. Through the integration of digital technology, companies can automate their production processes, increase visibility over operational performance, and make informed decisions. Prior to digitization, daily reporting often involved manually collecting data from various sources, such as production machines, operators, and physical work daily sheets. This can lead to errors in data entry, delays in processing and difficulty interacting data from different systems. This digitalization training aims to improve operational efficiency, improve data accuracy, and increase the accessibility of production information, such as knowing the process or flow in making daily reports to visualizing production data so as to make it easier for the Operations and Management Team to monitor factory productivity.